Test-beam demonstration of a TORCH prototype module. Issue 1 (1st November 2022) - Smallwood, J C; Bhasin, S; Blake, T; Brook, N H; Cicala, M F; Conneely, T; Cussans, D; van Dijk, M W U; Forty, R; Frei, C; Gabriel, E P M; Gao, R; et al.
Abstract : The TORCH time-of-flight detector is designed to provide a 15 ps timing resolution for charged particles, resulting in π /K particle identification up to 10 GeV/c momentum over a 10 m flight path. Cherenkov photons, produced in a quartz plate of 10 mm thickness, are focused onto an array of micro-channel plate photomultipliers (MCP-PMTs) which measure the photon arrival times and spatial positions. A half-scale (660 × 1250 × 10 mm 3 ) TORCH demonstrator module has been tested in an 8 GeV/c mixed proton-pion beam at CERN. Customised square MCP-PMTs of active area 53 × 53 mm 2 and granularity 64 × 64 pixels have been employed, which have been developed in collaboration with an industrial partner. The single-photon timing performance and photon yields have been measured as a function of beam position in the radiator, giving measurements which are consistent with expectations. The expected performance of TORCH for high luminosity running of the LHCb Upgrade II has been simulated.